Casting Light and Doubt on Uncontrolled DCDD Protocols - Rodríguez-Arias, David (The Hastings Center report, 2013)
The ever-increasing demand for organs led Spain, France, and other European countries to promote uncontrolled donation after circulatory determination of death (uDCDD). For the same reason, New York City has recently developed its own uDCDD protocol, which differs from European programs in some key ways. The New York protocol incorporates a series of technical and management improvements that address some practical problems identified in response to European uDCDD protocols. However, the more fundamental issue of whether uDCDD donors are dead when organs are procured remains problematic for the New York City protocol and, indeed, for all uDCDD protocols. In the United States, two amendments to the legal criteria of death have been suggested to avoid a formal violation of the dead donor rule in DCDD protocols: first, replacing the requirement “irreversible” with the weaker term “permanent,” and second, using the term “circulatory” instead of “cardiac” to identify the key function that must be lost to declare death. While intended to facilitate controlled DCDD, these modifications create a problem for uDCDD protocols: if extracorporeal membrane oxygenation is introduced to preserve the organs, then circulation is restored after death is declared. In this issue of the Hastings Center Report, Kevin Munjal and colleagues call for a new ethical construct and policy so that uncontrolled and controlled DCDD can coexist.